A biocompatible and pH-responsive nanohydrogel based on cellulose nanocrystal for enhanced toxic reactive oxygen species generation. (15th April 2021) - You, Chaoqun; Ning, Like; Wu, Hongshuai; Huang, Chaobo; Wang, Fei
Highlights: A biocompatible ROS generator for efficient chemodynamic therapy was developed. The Fe 3+ catalyzes H2 O2 to produce O H, which further leads to oxidative damage. The DPA increased the adhesion to cells and the 5-ALA increased ROS production. The loaded PTX was able to combine with ROS to efficiently kill tumor cells. Abstract: Traditional therapeutic regimens are currently far from satisfactory, and the integration of biocompatible carbohydrate polymers and nanotechnologies with conventional therapeutics has become a focus of research in cancer therapy. Herein, A novel biocompatible and pH-responsive nanohydrogel composed of two functional polymeric chains was developed from cellulose nanocrystals (CNCs) and 5-aminolevulinic acid (ALA), or dopamine (DPA). The biological molecules PDA and ALA were respectively conjugated to CNC through the coordination of iron ions to form two functional polymeric chains (PDA/Fe@CNC and ALA/Fe@CNC). The PDA/Fe@CNC chain increased the adhesion of the nanohydrogels to cells, while the ALA/Fe@CNC chain significantly increased reactive oxygen species (ROS) production. Furthermore, PTX molecules loaded into the nanohydrogels combined with ROS to efficiently kill tumor cells. The nanohydrogels displayed excellent cell affinity, high ROS yield (8.0-fold greater than that in control), and strong cytotoxicity (2.7 % of cell viability). The present study highlights the great potential of biocompatible natural polysaccharide-based materials for biomedical applications, and provides a new strategy for reducing the toxicity and side effects associated with traditional chemotherapy, demonstrating a novel antitumor treatment paradigm with high-efficiency but with only minor side effects.